Pelatihan Pembuatan Website HTML Menggunakan VS Code Di SMP Xaverius Maria Palembang - Fellycia Caroline; Serenity Devina Suryanto; Raphael Lee; Jonathan Jason Constantine; Daniel Udjulawa; Muhammad Rizky Pribadi (Pakis Journal Institute, 2026)
The development of digital technology requires students to possess basic skills in utilizing technology creatively and productively, including creating simple websites. However, most students still do not understand the basic process of website development. This community service activity aimed to provide training on creating profile websites using HTML with the assistance of Visual Studio Code for class 9 students at SMP Xaverius Maria Palembang. The methods used in this activity were community education and hands-on training through material presentation, demonstrations, independent practice, discussions, and evaluations. The results showed that participants were able to understand the basic structure of HTML and follow the process of creating simple websites properly. In addition, participants showed high enthusiasm during the activity and began to understand the fundamentals of simple website development. This activity provided new experiences for participants and helped improve students’ knowledge and interest in the field of information technology.